Smart Strategies To Prevent Acl Injuries: What Does The Research Say About Fifa 11+? - Sigit, Miftahudin; Wijaya, Habibi Hadi; Damai, A.Ine Aprilia; Alviana, Irana Mery (Institut Teknologi Bandung, 2025)
Background: Anterior cruciate ligament (ACL) injury is one of the most serious and frequently occurring injuries among youth football players. Such injuries not only disrupt athletic performance and training continuity but also pose long-term risks to an athlete's career and knee joint health. Neuromuscular-based preventive approaches have become a central focus in modern sports science to reduce the incidence of non-contact injuries. Objective: This systematic review aims to evaluate the scientific evidence regarding the effectiveness of the FIFA 11+ program in reducing the risk of ACL injuries among adolescent and young football players. Methods: A comprehensive literature search was conducted through PubMed, Scopus, ScienceDirect, and Google Scholar for studies published between 2008 and 2024. The inclusion criteria included randomized controlled trials (RCTs), prospective cohort studies, and systematic reviews or meta-analyses that assessed the impact of the FIFA 11+ program on ACL injury prevention. Results: A total of 10 studies met the inclusion criteria. Most of these studies demonstrated that implementation of the FIFA 11+ program reduced ACL injury risk by 30–77%, improved neuromuscular stability, and enhanced postural control and dynamic balance. The program's effectiveness was highly influenced by coach adherence, supervision quality, and training frequency of at least two to three sessions per week. Conclusion: The FIFA 11+ program has been proven to be an effective, low- cost, and easily implementable warm-up strategy for ACL injury prevention among youth football players in Indonesia. It has the potential to serve as a sustainable national model for neuromuscular-based injury prevention. Keywords: ACL injury, injury prevention, FIFA 11+, neuromuscular training, youth football, coach education